The Use of GPS Technology to Improve the Arrival Time of Customers to the Work Site - Aeesha Sdeek Shaheen (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
At present, there are many countries with a medium economic level and also a low level that has no public transport network such as the tram or metro, not even a bus network or School Bus Routing but transportation is done by private efforts that the state does not participate in. These efforts may be represented by taxi owners and owners of medium and small private buses that adopt to transfer Students, employees, and workers from their homes to places of work with monthly wages. nThis private transportation process faces several problems on the part of the user, who is the student, employee, or worker, such as the difficulty of finding the driver near the place of residence or finding a group of participants in the same vehicle whose places are near his place of residence, or if their housing is located on the road leading to the workplace like school or university, the time also if suits to everyone in terms of time to start work and time to end work. From the other part the vehicle owner, he finds it difficult to find better customers in terms of their nearest to the place of residence of the vehicle owner, or it is located on the road leading to the place of work. The second problem is finding the shortest road that passes through all the subscribers in the vehicle with less time and less cost which has been treated in an application called Ishtraki whereby the participants from students, employees, and workers are distributed to the closest vehicle driver and then find the best road for each vehicle driver as a road map to use it to reach all his participants as the shortest way.